Reversed phase HPLC for strontium ranelate: Method development and validation applying experimental design - Kovács Béla; Kántor Lajos Kristóf; Croitoru Mircea Dumitru; Kelemen Éva Katalin; Obreja Mona; Nagy Előd Ernő; Székely-Szentmiklósi Blanka; Gyéresi Árpád (Acta Pharmaceutica)
A reverse-phase HPLC (RP-HPLC) method was developed for strontium ranelate using a full factorial, screening experimental design. The analytical procedure was validated according to international guidelines for linearity, selectivity, sensitivity, accuracy and precision. A separate experimental design was used to demonstrate the robustness of the method. Strontium ranelate was eluted at 4.4 minutes and showed no interference with the excipients used in the formulation, at 321 nm. The method is linear in the range of 20–320 μg mL−1 (R2 = 0.99998). Recovery, tested in the range of 40–120 μg mL−1, was found to be 96.1–102.1 %. Intra-day and intermediate precision RSDs ranged from 1.0–1.4 and 1.2–1.4 %, resp. The limit of detection and limit of quantitation were 0.06 and 0.20 μg mL−1, resp. The proposed technique is fast, cost-effective, reliable and reproducible, and is proposed for the routine analysis of strontium ranelate.